Analysis of Legal Protection for Consumers and Businesses in E-Commerce Transactions - Shafira Zahru; Alip Rahman; Anom Sutrisno (International Journal Labs, 2026)
The rapid growth of e-commerce has transformed trading systems, offering convenience, broader product access, and cost efficiency. However, it also presents legal challenges, particularly regarding consumer protection and the accountability of business actors for defective or non-conforming products. Frequent complaints indicate systemic issues in product quality and information transparency, highlighting the need for effective legal frameworks to ensure fairness and trust in digital transactions. This study aims to analyze legal protection for consumers and business actors in Indonesian e-commerce, focusing on rights, obligations, and the enforcement of liability in multilateral digital transactions. Normative legal research was employed, using legislative and conceptual approaches to examine primary, secondary, and tertiary legal sources, including the Consumer Protection Law, the Civil Code, the Electronic Information and Transactions Law, and Government Regulation No. 80 of 2019. The results indicate that consumers are safeguarded through rights to accurate product information, product safety, and compensation for losses, while business actors are provided with legal certainty and protection from bad-faith claims. The discussion highlights the balance between preventive and repressive protections and the enforcement of strict liability for non-conforming products. In conclusion, the existing legal frameworks effectively establish fairness, accountability, and trust in e-commerce. Future research could investigate implementation challenges across platforms and the impact of emerging technologies on legal compliance and consumer protection.